Trace element and stable isotope data analyzed in core topes and a core sediment from the eastern equaterial Atlantic - Syee Weldeab (PANGAEA, 2022)
The foraminiferal trace element and carbon and oxygen isotope were analyzed in core tops and core sediment from the eastern equatorial Atlantic. The down core analyses were carried out to reconstruct climatic conditions during Eemian.